MODEL PENCEGAHAN KDRT BERBASIS MANAJEMEN KONFLIK DALAM Q.S. AL-NISA (04) : 34-35 - Abu Bakar, Abd. Syukur (PSW, 2015)
The existence of conflict as unavoidable phenomenon in the domestic environment requires good conflict management. The good conflict management is expected to change the negative effect of the conflict to be positive effect. At least, the conflict management can decrease the domestic violences that generally put women as the victims of the men. To apply good conflict management, Q.S. al-Nisa (04) : 34-35 can be an inspiration by starting the management conflict between husband and wife, hakam involvement from both of them, as well as the God involvement by His guidance